Impact of the COVID-19 pandemic on the mental health and well-being of UK healthcare workers - James Gilleen; Aida Santaolalla; Lorena Valdearenas; Clara Salice; Montserrat Fusté (BJPsych Open, 2021)
Background The coronavirus disease 2019 (COVID-19) pandemic has had a significant psychological impact on healthcare workers (HCWs).